FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP TINGKAT UNDERPRICING SAHAM PADA SAAT INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA TAHUN 2010 - 2014 - Ruben Novandri; Darsono Darsono (Diponegoro Journal of Accounting, 2016)
This research aims to analyze factors that affect underpricing stock rate at initial public offering in Bursa Efek Indonesia year 2010 – 2014. Dependent variable in this research is underpricing rate and the independent variables are underwriter reputation, return on asset (ROA), earning per share (EPS) and companies age. This research uses secondary data derived from prospectus and company financial reports which do IPO year 2010 – 2014.  Sample in this research amounted to 86 companies. This research uses purposive sampling method and multiple linear regression as an analysis tool. Prior to regression test, firstly the data is tested using classic assumption test. The results of this research indicate that the underwriter reputation, return on asset (ROA) have a negative significant affect to underpricing rate. Earning per share (EPS) has a negative unsignificant affect to underpricing rate. Companies age has a positive unsignificant affect to underpricing rate.